Supplementing an immunomodulatory feed ingredient to modulate thermoregulation, physiologic, and production responses in lactating dairy cows under heat stress conditions - Leiva, T. [UNESP]; Cooke, R. F.; Brandao, A. P. [UNESP]; Schubach, K. M.; Batista, L. F. D. [UNESP]; Miranda, M. F. [UNESP]; Colombo, E. A. [UNESP]; Rodrigues, R. O. [UNESP]; Junior, J. R. G. [UNESP]; Cerri, R. L. A.; Vasconcelos, J. L. M. [UNESP] (Elsevier B.V., 2017)
This study compared vaginal temperature, physiologic, and productive parameters in lactating dairy cows supplemented or not with Omnigen-AF (Phibro Animal Health, Teaneck, NJ) during the summer months in a tropical environment. Thirty-two lactating, primiparous (n = 16) and multiparous (n = 16) pregnant Holstein x Gir cows were ranked by parity, days in milk, body weight, and body condition score (BCS), and assigned to receive (SUPP; n = 16) or not (CON; n = 16) Omnigen-AF (Phibro Animal Health, Teaneck, NJ) at 56 g/cow daily (as-fed basis). During the experimental period (d -6 to 56), cows were maintained in a single drylot pen with ad libitum access to water and a total mixed ration, and milked twice daily. Cows received Omnigen-AF mixed with 200 g of corn (as-fed basis) after the daily morning milking through self-locking head gates, whereas CON cows concurrently received 56 g of kaolin mixed with 200 g of corn. For feed intake evaluation, cows from both treatments were randomly divided in 4 groups of 8 cows each, and allocated to 8 individual feeding stations for 3 d. Intake was evaluated 4 times per group from d 1 to 56. From d -6 to 0, d 15 to 28, and d 43 to 56, cow vaginal temperature was recorded hourly. Environmental temperature-humidity index (THI) was also recorded hourly from d 15 to 28 and d 43 to 56. Cows were evaluated for body weight and BCS on d -6 and 56, individual milk production was recorded daily from d -6 to 56, and milk samples were collected on d -6, 0, 7, 14, 21, 28, 35, 42, 49, and 56 for analyses of somatic cell count and milk components. Blood samples were collected on d -6, -3, 0, 9, 15, 18, 21, 24, 27, 36, 45, 48, 51, 54, and 56. Results from samples or observations collected from d -6 to 0 were included as an independent covariate in each respective analysis. Environmental THI was 74.2 +/- 0.5 and cows were exposed to THI >68 for 633 h within a total of 672 h of evaluation. Cows assigned to CON had greater vaginal temperature on d 28, 43, 45, and from d 48 to 55 (by 0.38 to 0.52%), as well as greater mean somatic cell count (by 97%) and serum haptoglobin concentrations (by 89%) compared with SUPP cows. Cows assigned to SUPP had greater mean dry matter intake (by 7%), BCS on d 56 (by 11%), and mean serum insulin concentrations (by 35%) compared with CON cows. Hence, SUPP ameliorated hyperthermia, improved nutritional status, and modulated systemic and mammary gland immune parameters in lactating dairy cows exposed to heat stress conditions.
Keywords: heat stress; lactating cow; milk production; Omnigen-AF; temperature